Ion pair-induced conformational motion in calix[4]arene-strapped calix[4]pyrroles. Issue 2 (11th December 2014) - Kim, Sung Kuk; Lynch, Vincent M.; Hay, Benjamin P.; Kim, Jong Seung; Sessler, Jonathan L.
Abstract : Cone- and conformationally mobile calix[4]arene-strapped calix[4]pyrroles bind cesium salts via various different binding modes. Abstract : In order to understand the still-poorly understood interplay between calix[4]arene conformations and cation and anion recognition in multicomponent systems, the ion pair receptors1 and2 were synthesized. In solution and in the solid state, the calix[4]arene subunit of receptor1 adopts a cone conformation, while that of2 interconverts between the cone and the partial cone conformation. These geometric features differ from previous systems where the calix[4]arene moiety was locked in the 1, 3-alternate conformation. A combination of 1 H NMR spectroscopic analyses and single crystal X-ray diffraction studies reveal that receptor1 binds the fluoride and the chloride anion via significantly different binding modes, displaying, for instance, 1 : 1 and 2 : 3 binding stoichiometries with CsF and CsCl, respectively. In the case of2, the conformation of the calix[4]arene constituent of2 is highly dependent on the size and quantity of anions present. For example, upon treatment of2 with the fluoride anion (as both the TBA + and Cs + salts), the calix[4]arene unit coexists as cone and partial cone conformers that are inter-convertible. In the presence of excess CsF, the aromatic rings of the calix[4]arene subunit becomes locked in the pinched cone conformation with the result that an ion pair-mediated coordination polymer is formed. In the presence of excess CsCl, the calix[4]arene unit of2 adopts only the partial cone conformation stabilized by aryl CH–anion hydrogen bonding interactions. The present systems constitute a rare set of related receptors wherein the effects of conformational changes are so tightly coupled with ion recognition.